2019
DOI: 10.1002/nau.24018
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in a contemporary cohort undergoing sacral neuromodulation using optimized lead placement technique

Abstract: Aims To evaluate factors associated with progression to stage 2 sacral neuromodulation (SNM) for refractory overactive bladder, urinary retention, or fecal incontinence using optimal lead placement techniques with curved stylet. Methods This is a retrospective analysis of a prospectively collected database of all consecutive stage 1 SNM lead placements at our institution between August 2014 and May 2017 using optimal lead placement technique with curved stylet. Patients with refractory overactive bladder, urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…As reported previously, 4 we hypothesize that several factors may contribute to the high therapy responder rate. A recent study by Adelstein et al 9 (2019) showed that high trial success rates (88%) can be achieved by optimal lead placement which includes the use of the curved stylet. The adoption of best practice techniques 5,10,11 for optimal lead placement undoubtedly contributed to the success in this study as evidenced by the 88% responder rate at 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, 4 we hypothesize that several factors may contribute to the high therapy responder rate. A recent study by Adelstein et al 9 (2019) showed that high trial success rates (88%) can be achieved by optimal lead placement which includes the use of the curved stylet. The adoption of best practice techniques 5,10,11 for optimal lead placement undoubtedly contributed to the success in this study as evidenced by the 88% responder rate at 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of these results shows that most of the participants were well‐above the traditional criteria for therapy success defined as a greater than 50% reduction in UUI episodes. The high clinical efficacy of the study results is likely influenced by the use of optimal lead placement techniques, 8,15–17 minimal lead migrations, and the constant‐current stimulation provided by the Axonics System. Additional studies are necessary to understand the impact of these and other factors on therapy success.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized implant technique using the curved stylet leading to intra-operative motor thresholds below 2 mA, could attribute to the improved outcome. In patients with such low motor thresholds, success rates of 89% have been reported in short term for patients with overactive bladder, nonobstructive urinary retention, or FI (5,10,11). Long-term efficacy remains to be proven.…”
Section: Discussionmentioning
confidence: 99%